Changes of the financial system in the context of the financial crisis - Da Cunha Ferreira, Beatriz Filipa; Brůna, Karel, 1973-; Šímová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
This thesis analyses the changes that have occurred in the financial system in the context of financial crises. To this end, a comprehensive review of the theoretical and empirical literature is conducted to identify the causes and effects of these crises, as well as the policies implemented to mitigate their impact. We also discuss the lessons we can learn from them and the potential solutions that can be explored to avoid future crises. The role of technology in facilitating these changes is also considered, with a particular focus on stress testing, artificial intelligence, and blockchain technology. Overall, this thesis provides valuable information on the changes in the financial system due to financial crises and sheds light on the ongoing evolution of the global financial system.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses